Dementia in a woman with Prader–Willi syndrome - Sinnema, Margje; Schrander-Stumpel, Constance T.R.M.; Verheij, Hans E.G.; Meeuwsen, Mireille; Maaskant, Marian A.; Curfs, Leopold M.G. (European journal of medical genetics, 2010)
We report on a 58-year-old woman with Prader–Willi syndrome (PWS) and dementia. This case report illustrates a new research area in older adults with PWS. Dementia might be associated with PWS. In the case of dementia, more clinical studies are warranted to observe whether premature Alzheimer changes or indications of other dementia forms indeed occur more prevalent in people with PWS.